2019
DOI: 10.1108/ics-03-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Socio-technical systems cybersecurity framework

Abstract: Purpose This paper aims to identify and appropriately respond to any socio-technical gaps within organisational information and cybersecurity practices. This culminates in the equal emphasis of both the social, technical and environmental factors affecting security practices. Design/methodology/approach The socio-technical systems theory was used to develop a conceptual process model for analysing organisational practices in terms of their social, technical and environmental influence. The conceptual process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 54 publications
4
49
0
Order By: Relevance
“…In studies [50] and [66], authors demonstrate that cybersecurity self-efficacy can influence individuals' intentions to strengthen their cyber hygiene practices. In cyber hygiene, self-efficacy is a part of the appraisal in which a significant predictor of security behaviour is linked to the individual's confidence in performing the security behaviour [83] and [68].…”
Section: ) Self-efficacymentioning
confidence: 99%
See 3 more Smart Citations
“…In studies [50] and [66], authors demonstrate that cybersecurity self-efficacy can influence individuals' intentions to strengthen their cyber hygiene practices. In cyber hygiene, self-efficacy is a part of the appraisal in which a significant predictor of security behaviour is linked to the individual's confidence in performing the security behaviour [83] and [68].…”
Section: ) Self-efficacymentioning
confidence: 99%
“…There are individual differences among men and women's cyber hygiene habits. The authors in [1] also explained that women had been found to create weaker passwords and updated software less often than males; it is also given that males had more knowledge about cyber hygiene than females [27], [50].…”
Section: A: Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…Personal privacy and security are challenges of global data information sharing (Chatterjee, 2019). On the other hand, new ways of business operations bring embedded cybersecurity issues (Malatji et al, 2019).…”
Section: Technological Aspectsmentioning
confidence: 99%